The Effects of Dexamethasone on Postoperative Complications After Surgical Removal of Impacted Lower Third Molar Teeth - Haider Ali Rassul; Ahmad Fliah Hassan; Athil Adnan Raheem; Hajer Ibrahem (College of Pharmacy / Mustansiriyah University, 2014)
The purpose of this study was to evaluate the effects of dexamethasone on postoperative complications after surgical removal of impacted lower third molar. Sixty patients submitted for surgical removal of impacted lower third molar, thirty patients received dexamethasone ampoule I.M (8 mg/2 ml) one hour preoperatively followed by one ampoule 12 hours post operatively, compared with another thirty patients who did not receive dexamethasone. The parameters of comparison were swelling and trismus depending on the patient's outcome (Yes or No), in addition to pain using VAS scale. Findings were recorded at second, fourth, and seventh days postoperatively. Dexamethasone appear to have great effect on reducing the post operative complications (pain, swelling and trismus) after the surgical removal of lower third molar and the statistical analysis showed a highly significant difference between group one that received dexamethasone and group two without dexamethasone. We concluded that the dexamethasone was statistically more efficient in reducing the pain, swelling and trismus